FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PT PTK - IVAN KANEL (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of research is to get empirical evidence of the influence of user involvement in the development process accounting information systems, personal technical ability Accounting Information Systems, the size of the organization and support of top management in the process of development and operation of Accounting Information Systems on performance of information system. The method of data collection in this study is the use of questionnaires. A questionnaire was distributed to 20 consultants in PT PK previously replied to the confirmation of filling the questionnaire. The analysis tool used is a correlation. The results showed that the involvement of users in the development of the SIA has no effect on the results and user satisfaction. SIA personal technical ability has no effect on satisfaction and usage. The size of the organization has no effect on user satisfaction. While top management support positive effect on user satisfaction.